Transforming Ability of Bacterial Deoxyribonucleic Acid in Relation to the Marker Efficiencies in Diplococcus pneumoniae During Thymidine Starvation - Brunel, F. (1971)
Thymidine starvation induces a decrease in transforming activity of pneumococcus deoxyribonucleic acid. The integration of low- and high-efficiency markers seems to be equally affected.